Strategic Management for Photovoltaic Power System and Development in Developing Countries - Hiranvarodom, Somchai (Frontiers in Engineering Innovation Research, 2003)
The process of information dissemination for the successful implementation for photovoltaic (PV) programme in developing countries is necessary. It is essential to consider the modelling for implementation of a PV project to ensure that it will be successful. This paper proposes a modelling of strategic management for PV power system and development. The roles of key players in the modelling and the implementation of the strategy and the responsibilities of these organizations are addressed.